An Unusual Case of Recurrent Limb Pain in Childhood - Mesquita, Marta (2019)
Recurrent limb pain may be the first and only manifestation of migraine in childhood. However, the temporal relation of limb pain with headache is unusual, making migraine limb pain difficult to diagnose. A six-year-old boy was referred with “growing pains” in the last four years. He presented recurrent attacks of bilateral shin pain, typically developing during the night but also in the morning, two or more times per week. He became pale during episodes and always needed analgesics for pain relief. Physical examination and investigation were normal.  His father had “growing pains” and migraine since his childhood. The treatment with propranolol resulted in significant improvement of frequency and severity of episodes. Considering the prevalence of migraine and “growing pains” in population, we suggest that migraine limb pain may be underdiagnosed. In children with recurrent limb pain and personal or family history of migraine, migraine limb pain diagnosis must be considered.